Overview of Evidence Based Practices in Nursing - Ebru Öztürk Çopur; Nilgün Kuru; Çiğdem Canbolat Seyman (Association of Nurse Managers, 2015)
Nowadays, aging of society, increase of chronic diseases caused to use high cost of drugs and treatment methods. The best approach are evidence-based practice (EBP) for appropriate use of resources. There are many reasons increasing the importance of EBP. These are to increase rate of medical errors in patient care and information demands of patients, to decline trust on health professionals. Also, EBP are scientize the diagnosis, treatment and care process. Evidence-based health care is defined as combining appropriate resources, patient preferences, expert opinion and the evidence obtained from scientific research. To develop EBP in nursing, knowledge and skills in this area must be increased and the barriers in front of nursing care practices based on scientific data must be removed. There're many individual and organizational barriers about EBP of nurses. Individual barriers like the inability critically appraise or synthesize the research literature and lack of search skills. Organizational barriers for nurses are the lack of time to apply research results. Besides, the lack of organizational support should be taken into consideration for the reason why the nurses do not believe that they have the power and self determination to apply the changes to the patients in case of significant circumstances. The main condition of being a professional nurse is surely to understand the science and scientific method properly and to reflect these to the job. In the future,due to the researches which was made by using scientific methods nurses will be more aware to make evidence-based decisions rather than experience-based ones. Producing its own knowledge, nursing will take more responsibility for the scientific value of and the use of knowledge. However, it is necessary to work with a team which produces researches and uses evidences of these in order to achieve this.